Comparative transcriptome analysis and CRISPR/Cas9 gene editing reveal that E4BP4 mediates lithium upregulation of Per2 expression. Issue 12 (15th December 2021) - Zhou, Qin; Wang, Kankan; Qiu, Jiameng; Zhu, Di; Tian, Tian; Zhang, Yunfei; Qin, Ximing
Abstract : Abstract : Bipolar disorder (BPD) is a psychiatric disorder characterized by alternate episodes of mania and depression. Disruption of normal circadian clock and abnormal sleep cycles are common symptoms of BPD patients. Lithium salt is currently an effective clinical therapeutic drug for BPD. Animal and cellular studies have found that lithium salt can upregulate the expression of the clock gene Per2, but the mechanism is unknown. We aim to understand the mechanism underlying the Per2 upregulation by lithium treatment. By taking approaches of both comparative transcriptome analysis and comparative qPCR analysis between human and murine cells, Lumicycle assay, luciferase assay and RT-qPCR assay showed that lithium could significantly upregulate the expression of Per2 in both mouse and human cells, and significantly inhibit the expression of E4bp4, which encodes a transcriptional inhibitor of Per2 . After knocking out the cis-element upstream on the Per2 promoter that responds to E4BP4, the upregulation effect on Per2 by lithium disappeared. When E4bp4 gene was knocked out, the upregulation effect on Per2 by lithium salt disappeared. This study has found that lithium upregulates Per2 expression by reducing the expression of transcription factor E4BP4, but the mechanism of lithium salt downregulation of E4BP4 remains to be further studied. Our study provides a new therapeutic target and approaches for treating BPD.